The role of serum endothelin-1 level in the etiopathogenesis of central serous chorioretinopathy - Turkcuoglu, Peykan; Kadayifcilar, Sibel; Eldem, Bora (Elsevier Science Inc, 2006)
PURPOSE: To assess the role of serum endothelin,l (ET,I) in the pathogenesis of central serous chorioretinopathy (CSC). DESIGN: Prospective, case control study. METHODS: The serum ET,1 levels of 21 otherwise healthy patients who received a diagnosis of acute CSC (group 1) were measured with the enzyme-linked immunosorbent assay (ELISA) method at the initial visit, at the one month follow-up examination, and after complete angiographic resolution of the leakage. Nine patients with a previous diagnosis of CSC (group 2), 10 patients from the outpatient clinic (group 3), and 14 hospital employees (group 4) were also included. RESULTS: The serum ET,I levels in group I revealed neither correlation with the disease activity nor significant difference from the levels in groups 2 and 4. However, serum ET-1 levels in group 3 were statistically higher than the levels in groups I and 4. CONCLUSION: These findings suggest no role of serum ET,1 in pathogenesis of CSC in otherwise healthy subjects.
37th Annual Meeting of the Turkish-Ophthalmological-Society -- 2003 -- Istanbul, TURKEY